On the central limit problem for sums of random variables defined on a Markov process with discrete parameter - Aleškevičius, G. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Г. Ю. Алешкявичюс. О центральной предельной проблеме для сумм случайных величин, заданных на цепи Маркова G. Aleškevičius. Atsitiktinių dydžių, apibrėžtų Markovo grandinėje, sumų centrinės ribinės problemos klausimu